A bipolar electrochemiluminescence sensing platform based on pencil core and paper reservoirs. Issue 30 (8th March 2016) - Lu, Wen-Xiu; Bao, Ning; Ding, Shou-Nian
Abstract : A very simple, portable and disposable BPE-ECL sensing platform has been investigated using commercial pencil core and paper cells. Abstract : In this work, a novel closed bipolar electrochemiluminescence (ECL) sensing platform based on a commercial pencil core and paper reservoirs was described for the first time. A pencil core functioned as a bipolar electrode and the Ru(bpy)3 2+ /(NH4 )2 C2 O4 was used as the electrochemical reaction system to generate the ECL signal in existing model targets.